Hydrobiological studies within the tea gardens at Srimangal, Bangladesh. VI. Desmids (Xanthidium, Arthrodesmus, Staurodesmus and Staurastrum) - Islam, AKM Nurul; Irfanullah, Haseeb Md (Bangladesh Journal of Plant Taxonomy, 2006)
In this last instalment of the series, 78 desmid taxa belonging to four genera, namely Xanthidium (8 taxa), Arthrodesmus (3 taxa), Staurodesmus (11 taxa) and Staurastrum (56 taxa) have been recorded from different aquatic habitats located within the tea gardens at Srimangal, Maulvi Bazar. Of these, nine are described as new records for Bangladesh. An overall assessment of the algal flora of the study area reveals desmids as the single largest group consisting of 230 taxa out of 421 recorded algal taxa. The paper comments on the conservation potentials of the studied aquatic habitats as monitoring tools of land use pattern like tea-gardening. Key words: Acidic habitats, Species diversity, Conservation, Phytoplankton, New records DOI: 10.3329/bjpt.v13i2.583 Bangladesh J. Plant Taxon. 13(2): 111-129, 2006 (December)